2022
DOI: 10.3390/bios12070549
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Orientation Invariant Heuristic Features with Variant Window Length of 1D-CNN-LSTM in Human Activity Recognition

Abstract: Many studies have explored divergent deep neural networks in human activity recognition (HAR) using a single accelerometer sensor. Multiple types of deep neural networks, such as convolutional neural networks (CNN), long short-term memory (LSTM), or their hybridization (CNN-LSTM), have been implemented. However, the sensor orientation problem poses challenges in HAR, and the length of windows as inputs for the deep neural networks has mostly been adopted arbitrarily. This paper explores the effect of window le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A more detailed explanation of the features can be found in [ 26 ]. Although they introduced the nine features mentioned and used them to eliminate the orientational effect, in a previous study [ 69 ], we found the first four features and to be the most significant and effective in reducing the orientational effect. Therefore, for our study, we only used the first four features.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…A more detailed explanation of the features can be found in [ 26 ]. Although they introduced the nine features mentioned and used them to eliminate the orientational effect, in a previous study [ 69 ], we found the first four features and to be the most significant and effective in reducing the orientational effect. Therefore, for our study, we only used the first four features.…”
Section: Methodsmentioning
confidence: 85%
“…That means each window had 65 samples, and two consecutive windows had 64 samples in common. We used the window length of 65, because we found it to be both computational and time-efficient in our previous study [ 69 ]. The information for the validation approach is organized in Table 7 .…”
Section: Methodsmentioning
confidence: 99%
“…However, this includes the investigation to test the selected features with a variety of sensor placement locations, such as waist, wrist, chest, and ankle, sampling frequency, and the performance of the dataset. The purpose of [20] is to investigate the impact of window lengths with orientation invariant heuristic features on the performance of 1D-CNN-LSTM using data from 42 participants to recognize six human activities: sitting, lying down, walking, and running at three different speeds using information gathered from the Samsung Galaxy s7 smartphone's accelerometer sensor with the preinstalled Ethica application.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of the one-dimensional convolutional neural network (1D CNN) technique on the field of air-writing recognition has been substantial. Numerous studies have been conducted to investigate the application of deep convolutional neural networks (CNNs) in the field of air-writing recognition, and these investigations have consistently proved the efficacy of such networks [20], [29].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation